Incident detection and isolation in drilling using analytical redundancy relations. (August 2015) - Willersrud, Anders; Blanke, Mogens; Imsland, Lars
Abstract: Early diagnosis of incidents that could delay or endanger a drilling operation for oil or gas is essential to limit field development costs. Warnings about downhole incidents should come early enough to allow intervention before it develops to a threat, but this is difficult, since false alarms must be avoided. This paper employs model-based diagnosis using analytical redundancy relations to obtain residuals which are affected differently by the different incidents. Residuals are found to be non-Gaussian – they follow a multivariate t -distribution – hence, a dedicated generalized likelihood ratio test is applied for change detection. Data from a 1400 m horizontal flow loop test facility is used to assess the diagnosis method. Diagnosis properties of the method are investigated assuming either with available downhole pressure sensors through wired drill pipe or with only topside measurements available. In the latter case, isolation capability is shown to be reduced to group-wise isolation, but the method would still detect all serious events with the prescribed false alarm probability.